Portraits and Excuses of Religious Radicalism in Educational Institutions - Gazali, M.; Huda, Syamsul; Kurniawan, Edi (LETIGES, 2024)
This article is based on a portrait of religious radicalism among students in public and religious schools in Jambi Province. This is motivated by significant gaps in several studies that still need to integrate comprehensive quantitative and qualitative analysis. Therefore, this article provides a more thorough and nuanced understanding of this issue using a mixed methods sequential explanatory model. Sampling was non-probability covering 5 districts/cities, 15 public schools, 15 religious schools, and 750 respondents. The results show a high potential for radicalism: 47.6% of respondents are willing to join violent jihadist groups, 38.8% of respondents view Pancasila as incompatible with Islam, 89.4% of respondents support the implementation of Sharia law, and 82.8% are willing to join groups that want to establish an Islamic state. This analysis reveals that radicalism emerges due to disappointment with law enforcement in Indonesia. These findings underscore the importance of integrating national values ​​into the education curriculum and involving higher education institutions in fostering critical thinking about religion, national identity, and civic responsibility. This article has significant implications for policymakers, educators, and researchers seeking to develop effective strategies to counter radicalization while promoting religious understanding and national unity in Indonesia’s diverse society. As such, this article significantly contributes to efforts to understand and address the challenges of religious radicalism among Indonesia’s young generation.